ANALYZING THE PERFORMANCE OF ISLAMIC BANKING IN INDONESIA AND MALAYSIA: MAQASID INDEX APPROACH - Saoqi, Abdul Aziz Yahya (Universitas Muhammadiyah Prof DR HAMKA, 2017)
The discourse of the presence of Maqasid Index as an alternative approach to measure the performance of Islamic banking become broadly and extensively discussed among Islamic scholars. It is because the Islamic banking has different concept than the conventional bank both in theory and practice, thus the Islamic banks should have they own benchmark to measure their performance. Therefore, Maqasid Index which more directed at the aims and objectives of sharia, become proper benchmark to measure the performance of Islamic banking. This research would like to measure and to compare the performance of Islamic banking industry in Indonesia and Malaysia using Maqasid Index approach with SAW (Simple Additive the Weighting) method. The context of this research is Islamic banking industry in Indonesia and Malaysia which represented by Bank Syariah Mandiri from Indonesia and Bank Islam Malaysia Berhad from Malaysia. This research also will use secondary data from year 2013-2014. The result found that from the first and third objective (Education/ Tadlihb al-Fardh), Islamic bank in Malaysia which represented by BIMB depicted better performance which reached 38.37% while BSM depicted only 5.48%. For the second objective (Justice/ Al-Adl), BSM showed better performance which reached 17.33%. For the third objective (Welfare/ Maslahah), BIMB lead upon BSM which reached 103.25% and 78.89% accordingly. From the calculation of Maqasid Index rank, BIMB take the first place which reached 13.79%. Whilst, BSM take the second place of this Maqasid Index rank which reached 11.14%.